OBSERVATIONS ON THE BIOLOGY OF THE FEATHER-BACK, NOTOPTERUS NOTOPTERUS (PALLAS) - Parameswaran, S; Sinha, M (Indian Journal of Fisheries, 2011)
FEATHER-BACKS, comprising the genus Notopterus, are represented in India by two species, viz., N. notopterus and A’^. chitala, of which N. notopterus has a widespread distribution. It abounds in fresh and brackish waters from India to Malay Archipelago (Day, 1878). Though the species attains a maximum size of 6r0cm (Day, op. cit.), specimens beyond 40-0 cm were not encountered in the present study. Besides being consumed both in fresh and dry state, the species has many potential uses (Anon., 1962).